Tobacco and smoking in Cuba: from the agricultural economy to the health economy - Efraín Sánchez González; Fé Fernández Hernández (Medisur)
The cigarettes and tobacco consumption creates an externality that is more relevant in the detriment of the life quality and life expectancy experienced by the individual smoker,  in relation to those who do not consume cigarettes or tobacco. The psychosocial cost not financially quantified far exceeds any expectation of economic benefit. This article deals with the socioeconomic impact of smoking in Cuba. The economic distribution induced by smoking leads to the persistence of such socioeconomic inequity, which worsens with the number of smokers and the intensity of cigarette and tobacco consumption. This phenomenon contradicts the socialist principle of distribution according to work, where non-smokers should not bear the consequences of smoking and smokers themselves should not be induced to persist in smoking. The subtlety of the social costs attributable to smoking and the impact of the benefits of domestic and foreign trade do not allow a full assessment of the main effects of smoking from the socioeconomic aspect.